2000
DOI: 10.4269/ajtmh.2000.62.65
|View full text |Cite
|
Sign up to set email alerts
|

A case-control auditory evaluation of patients treated with artemisinin derivatives for multidrug-resistant Plasmodium falciparum malaria.

Abstract: Abstract. The artemisinin derivatives are now used widely in areas with multidrug-resistant Plasmodium falciparum malaria such as Southeast Asia, but concerns remain over their potential for neurotoxicity. Mice, rats, dogs, and monkeys treated with high doses of intramuscular artemether or arteether develop an unusual pattern of focal damage to brain stem nuclei (particularly those involved in auditory processing). To investigate whether a similar toxic effect occurs in patients treated with these compounds, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
36
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 23 publications
4
36
1
Order By: Relevance
“…Two case-control studies in which audiological measurements including ABR were performed in patients exposed to several courses of artemisinin derivatives reported no differences in the test results between cases and controls. 7,24 A more recent case-control study along the Thailand-Myanmar border performed pure-tone threshold and ABR tests in subjects treated with A-L within the previous 5 years and found no evidence of auditory brainstem impairment attributable to A-L. 25 Sim ilarly, a pure-tone threshold and ABR study in a limited number of healthy volunteers with experimentally induced malaria, treated with A-L, found no evidence of a detrimental drug effect on the auditory system. 26 In a randomized study in malaria patients from Ethiopia, pure-tone thresholds revealed statistically significant temporary threshold shift only in the quinine group, but this effect did not appear to be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Two case-control studies in which audiological measurements including ABR were performed in patients exposed to several courses of artemisinin derivatives reported no differences in the test results between cases and controls. 7,24 A more recent case-control study along the Thailand-Myanmar border performed pure-tone threshold and ABR tests in subjects treated with A-L within the previous 5 years and found no evidence of auditory brainstem impairment attributable to A-L. 25 Sim ilarly, a pure-tone threshold and ABR study in a limited number of healthy volunteers with experimentally induced malaria, treated with A-L, found no evidence of a detrimental drug effect on the auditory system. 26 In a randomized study in malaria patients from Ethiopia, pure-tone thresholds revealed statistically significant temporary threshold shift only in the quinine group, but this effect did not appear to be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Extensive clinical studies that included detailed neurologic testing and specific evaluation of auditory-evoked potentials have also reported no evidence for neurotoxic side effects of artemether. 31,32 Currently, the artemisinin drugs have been used in more than two million people with malaria, of whom more than ten thousand have been included in carefully monitored clinical trials, and no direct evidence for a clinically relevant neurotoxic effect in humans has been reported. The neurotoxicity reported in rodents, dogs, and monkeys has occurred with high doses.…”
Section: Discussionmentioning
confidence: 99%
“…No evidence of neurotoxicity has emerged in extensive clinical studies of the artemisinin derivatives, which have included detailed neurologic testing, and specific evaluation of auditory-evoked potentials. 10 This extensive clinical experience has given rise to increased confidence in the safety of this important class of antimalarial drugs.…”
Section: Discussionmentioning
confidence: 99%